EFFECTS OF INTRATHECAL BUPIVACAINE WITH NORMAL SALINE VERSUS BUPIVACAINE WITH FENTANYL IN PATIENTS UNDERGOING SURGERY - Jigna R Shah; Manish Bhatt (National Journal of Medical Research, 2016)
Objective:To know the effects of intrathecal 0.5% Bupivacaine 2.5 cc with 0.5 cc normal saline and 0.5% Bupivacaine 2.5 cc witth 25 μg fentanyl for various lower abdominal surgeries.